KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS XI SMA ALQUR'AN WAHDAH ISLAMIYAH KENDARI - Ahmad Kurniawan; Amirudin Rahim; La Ode Akhiri Zulzaman (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The purpose of this research is to describe the ability to write procedural texts of the 11th grade students of SMA Al-Qur’an Wahdah Islamiyah Kendari. The method used in this research is descriptive quantitative. This type of research falls into the category of field research. It is called field research because the researcher goes directly to the school where the research is conducted. Based on the results and analysis conducted, it can be concluded that out of 46 students in the 11th grade of SMA Al-Qur’an Wahdah Islamiyah Kendari, individually, 35 students (76.98%) are categorized as capable, and 11 students (23.91%) are categorized as not yet capable of writing procedural texts. This can be seen from the students' scores in the research. The structure of the procedural text includes: goal (100%), steps (95.65%), reaffirmation (91.30%). The linguistic features of procedural texts include: imperative verbs (95.65%), additive conjunctions (100%), persuasive statements (65.21%), technical terms (17.39%), tool descriptions (4.34%).